1989
DOI: 10.1007/bf01957467
|View full text |Cite
|
Sign up to set email alerts
|

Prothymosin alpha is not a nuclear polypeptide

Abstract: Using a radioimmunoassay for the NH2-terminus of prothymosin alpha, the crossreactive material was measured in subcellular fractions of calf thymus and liver. No significant amount of crossreactive material was found in the nucleus. This provides experimental evidence against a recent hypothesis, based on structural evidence, that prothymosin alpha is a nuclear polypeptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
10

Year Published

1990
1990
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
(1 reference statement)
0
8
0
10
Order By: Relevance
“…From the literature (16,17,20) it seems obvious that prothymosin, at least, is also found in the cytoplasm. This could be the result of specific removal of prothymosin from the nucleus by linkage to a small RNA, as described by Makarova et al (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the literature (16,17,20) it seems obvious that prothymosin, at least, is also found in the cytoplasm. This could be the result of specific removal of prothymosin from the nucleus by linkage to a small RNA, as described by Makarova et al (17).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the presence of a "nuclear localization signal" near the COOH terminus ofprothymosin and superficial structural similarities between prothymosin and a variety of nuclear proteins, Gomez-Marquez and Segade (19) proposed that it might function as a nuclear protein. Although a conventional cell-fractionation procedure yielded detectable levels of prothymosin only in the cytoplasmic fraction of calf thymus or liver (20), an elegant series ofexperiments by Watts et al (21,22) demonstrated that both prothymosin and parathymosin injected into Xenopus oocytes accumulated in the nucleus, in contrast to thymosin f84, which remained in the cytoplasm.…”
mentioning
confidence: 99%
“…In contrast, polyvalent antibodies to thymosin ␣ 1 highlighted immunoreactive material in the nuclei of bile duct cells but not hepatocytes (Fraga et al 1993), and distinguished "thymosin immunoreactive peptides" primarily in the nuclei of IEC-6 cells, a line derived from the small intestine of the rat (Conteas et al 1990). In disrupted cells, prothymosin ␣ was almost invariably cytoplasmic (Tsitsiloni et al 1989;Sburlati et al 1990). Therefore, these studies, too, failed to dispel the uncertainty surrounding the in vivo location of prothymosin ␣ .…”
Section: S U M M a R Ymentioning
confidence: 99%
“…Nevertheless, several investigations have questioned such immunological role based on its wide tissue distribution [2], its broad phylogenetic presence from yeast to man [3] and the absence of a signal peptide [4]. Moreover, since we postulated a nuclear location for ProTa [5], several contradictory data on its subcellular distribution have been reported, indicating either nuclear [6,7] or cytoplasmic localization [3,8]. However, microinjection of ProTa into the cytoplasm of Xenopus oocytes showed that this protein indeed migrates to the nucleus [6].…”
Section: Introductionmentioning
confidence: 99%